Analisis Dimensi Keberlanjutan Sistem Manajemen Lingkungan ISO 14001:2015 pada PT Indonesia Power UP-Mrica - Setiya Tiara; Tatan Sukwika; Kholil Kholil (ECOTAS, 2022)
The development of the company is always followed by technological developments to realize an environmentally friendly company, so it requires sustainable environmental management, such as implementing an Environmental Management System (SML) in accordance with ISO 14001:2015 standards. This research aimed to evaluate the fulfillment of iso 14001:2015 SML standards in a multidimensional manner. The research method used was descriptive research with a quantitative approach. The research phase was studied systematically, factually and accurately which was further connected with the GEMI-2017 method. The data was obtained through observation and in-person interviews with the management of PT Indonesia Power UP Mrica. The results of the study are known from the seven dimensions measured, there are three dimensions that are categorized as good, namely organizational context, planning, and support. While the other four dimensions are categorized as satisfactory sustainability, namely the dimensions of leadership, operations, performance evaluation and improvement. The conclusion is that the fulfillment of the implementation of the sustainability dimension on the environmental management system is in accordance with the GEMI-2017 ISO 14001:2015 method, as well as the implementation of the self-assessment checklist has a satisfactory category.